Synthesis of Na⁺,CO₃²⁻-containing calcium phosphate nanoparticles and their thermal transformations - Malyshenko, A.I.; Strutynska, N.Yu.; Zatovsky, I.V.; Slobodyanik, N.S.; Epple, M.; Prymak, O. (Functional Materials, 2014)
The nanoparticles of Na⁺,CO₃²⁻-containing hydroxyapatites have been prepared from aqueous solutions for system Na⁺-Ca²⁺-NO₃⁻-CO₃²⁻-PO₄³⁻ at molar ratio of Ca/P = 1.67:1 and CO₃²⁻/PO₄³⁻ = 0, 1.0, 2.0, 3.0. Thermal transformations of the obtained phosphates have been established for the temperature range of 80-900°C. The obtained complex-substituted HAP have been investigated using IR spectroscopy, scanning electron microscopy, X-ray diffraction and thermogravimetry.